Radio and optical techniques for locating equatorial plasma irregularities - Miller, Ethan Schofield (2009)
Irregularities in the plasma density, especially dynamic, turbulent irregularities, may have profound effects on radio waves passing through the ionosphere. A class of these equatorial F-region irregularities is the subject of this dissertation. This dissertation is primarily concerned with the behavior of the equatorial ionosphere and irregularities therein that degrade satellite radio communication and navigation systems. The remainder of this chapter is devoted to the equatorial ionosphere, its day-to-day behavior, and the irregularities that are produced there. Some of the outstanding problems will be identified, especially those addressed in this dissertation.